The Complexities of State Court Compliance with U.S. Supreme Court Precedent. (3rd April 2017) - Fix, Michael P.; Kingsland, Justin T.; Montgomery, Matthew D.
ABSTRACT: The United States Supreme Court has significant influence over the development of legal policy, yet it must rely on external actors to bring to fruition the desired effect of its decisions. Among the most important such actors are state high courts who are often motivated to issue decisions promoting policies at odds with the U.S. Supreme Court and who have mechanisms to legitimize such decisions. This study builds on existing work on state court compliance with U.S. Supreme Court precedent by introducing a new theoretical framework that accounts for the impact of state-specific precedent vitality, or the degree to which the high court of a specific state has positively treated a U.S. Supreme Court precedent, on state high court compliance. Our analysis of state high court treatment of Miller v. California provides strong evidence for the importance of state-specific vitality as a determinant of state high court compliance.